Myelofibrosis progression grading based on type I and type III collagen and fibrillin 1 expression boosted by whole slide image analysis - Székely, Tamás; Wichmann, Barna; Maros, Máté E.; Csizmadia, Annamaria; Bodor, Csaba; Timar, Botond; Krenacs, Tibor (Histopathology, 2023)
Aims: The progression of primary myelofibrosis is characterised by ongoing extracellular matrix deposition graded based on ‘reticulin’ and ‘collagen’ fibrosis, as revealed by Gomori's silver impregnation. Here we studied the expression of the major extracellular matrix proteins of fibrosis in relation to diagnostic silver grading supported by image analysis. Methods and results: By using automated immunohistochemistry, in this study we demonstrate that the expression of both types I and III collagens and fibrillin 1 by bone marrow stromal cells can reveal the extracellular matrix scaffolding in line with myelofibrosis progression as classified by silver grading. ‘Reticulin’ fibrosis indicated by type III collagen expression and ‘collagen’ fibrosis featured by type I collagen expression were parallel, rather than sequential, events. This is line with the proposed role of type III collagen in regulating type I collagen fibrillogenesis. The uniformly strong fibrillin 1 immune signals offered the best inter-rater agreements and the highest statistical correlations with silver grading of the three markers, which was robustly confirmed by automated whole slide digital image analysis using a machine learning-based algorithm. The progressive up-regulation of fibrillin 1 during myelofibrosis may result from a negative feedback loop as fibrillin microfibrils sequester TGF-β, the major promoter of fibrosis. This can also reduce TGF-β-induced RANKL levels, which would stimulate osteoclastogenesis and thus can support osteosclerosis in advanced myelofibrosis. Conclusions: Through the in-situ detection of these extracellular matrix proteins, our results verify the molecular pathobiology of fibrosis during myelofibrosis progression. In particular, fibrillin 1 immunohistochemistry, with or without image analysis, can complement diagnostic silver grading at decent cell morphology.